2010
DOI: 10.1007/s10669-010-9274-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring chemical analysis of vermicompost of various oil palm fibre wastes

Abstract: The aim of this work was to study the physical and chemical properties of different oil palm wastes, viz. empty fruit bunch (EFB), oil palm frond (OPF) and oil palm trunk (OPT). A study (84 days duration) was conducted to evaluate the efficiency of an exotic earthworm species (epigeic-African Nightcrawler (Eudrilus euginae)) for the decomposition of different types of oil palm wastes (EFB, OPT and OPF) into valuable vermicompost. The decrease in earthworm's biomass gain for EFB, OPT and OPF may be due to exhau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…The lowest growth rate of earthworm was recorded in the treatment supplied with empty fruit bunches alone (0.21 g/worm/day), and the highest was recorded in both treatments of E2:D1 and E1:D2 (0.54 g/worm/ day). It is hypothesized that the suitable proportion of cow dung and empty fruit bunches provided earthworms with sufficient amounts of easily degradable organic matter, which created an ideal environment for the growth and reproduction of earthworms (Nahrul Hayawin et al 2010). An initial increase in biomass was followed by stabilization, and later, weight loss was observed in most of the treatments after 12 weeks of vermicomposting process (Table 3).…”
Section: Growth Of E Eugeniae In Different Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lowest growth rate of earthworm was recorded in the treatment supplied with empty fruit bunches alone (0.21 g/worm/day), and the highest was recorded in both treatments of E2:D1 and E1:D2 (0.54 g/worm/ day). It is hypothesized that the suitable proportion of cow dung and empty fruit bunches provided earthworms with sufficient amounts of easily degradable organic matter, which created an ideal environment for the growth and reproduction of earthworms (Nahrul Hayawin et al 2010). An initial increase in biomass was followed by stabilization, and later, weight loss was observed in most of the treatments after 12 weeks of vermicomposting process (Table 3).…”
Section: Growth Of E Eugeniae In Different Treatmentsmentioning
confidence: 99%
“…Nahrul Hayawin et al (2010) carried out a research on vermicomposting of empty fruit bunches, oil palm trunk and oil palm frond Stocking density of treatment 1:6 (earthworm/ media) ratio using E. eugeniae with a precomposting (the duration of pretreatment was not stated), and their results showed that empty fruit bunches were the best substrates for E. eugeniae. The result obtained by Nahrul Hayawin et al (2010) showed that after 84 days of vermicomposting, C/N ratio of the vermicomposts was still remained high at about 36.49, indicating that the produced vermicomposts were not matured enough to be used as a suitable fertilizer because plants cannot assimilate nitrogen unless the C/N ratio is in the order of 20 or less (Khwairakpam and Bhargava 2009). Earlier, Sabrina et al (2009) carried out a research on vermicomposting of empty fruit bunches using three species of earthworms, namely Eisenia fetida, Pontoscolex corethrutus and Amynthas rodericensis, but only E. fetida was able to survive in empty fruit bunches.…”
Section: Nutrient Quality Of the Vermicompostmentioning
confidence: 99%
See 1 more Smart Citation
“…The study revealed that the bioconversion of WOC is possible by vermicomposting, although pre-composting of WOC reduced toxic compounds (polyphenols) and showed more initial stability than fresh wet olive cake (Table 3). Nahrul Hayawin et al (2009) conducted an 84 days study to evaluate the efficiency of Eudrilus eugeniae for the decomposition of different types of oil palm wastes, viz., empty fruit bunch (EFB), oil palm frond (OPF) and oil palm trunk (OPT) into valuable vermicompost. They reported that at the end of vermicomposting, organic C content decreased slightly in the vermicompost as compared to the initial level in all substrates and nitrogen content was greater in final products than in initial substrates.…”
Section: Oil Extraction Industries Wastementioning
confidence: 99%
“…Nahrul Hayawin et al (2010) studied the physicochemical changes of an oil palm biomass during vermicomposting. The data indicated that vermicomposting of an oil palm biomass, such as EFB, OPT, and OPF, is an appropriate method for recycling the oil palm wastes to a value-added vermicompost.…”
Section: Composting Of Palm Oil Biomassmentioning
confidence: 99%